Analisis Kebijakan Stabilitas Harga Gabah/ Beras di Tingkat Petani di Propinsi DIY - Arjayanti, Syam (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2010)
This paper evaluate the rice price stabilization policy in the province of DIY. The paper assesses the effectiveness of three policies, which include government purchase price policy (HPP), barns institutional development program and capital strengthening funds for rural economic enterprises program (DPM-LUEP), in maintaining rice price. Stability. Paper findings show that none of the three policies have been able to stabilize prices stable at the farmer level. However, of the policies, the HPP gives the greatest benefits compared to the other two policies.This is attributable to the fact that BULOGs rice procurement program helps in stabilizing rice prices by reducing the supply during harvest and increasing supply when rice price rise in the market. Some of the recommendations of this research include the need to improve BULOG performance, revitalization of collective barns, and simplification of DPM-LUEP administration and finance in enhancing the role of small-scale rural economic institutions.